The university teaching in the context of initial training: Academic-pedagogical challenges in evidence (Revista Contexto & Educação, 2023)
The research aimed to analyze the academic-pedagogical challenges in the teaching and learning process in the context of university teaching by professors of the Instituto de Educação, Agricultura e Ambiente (Amazonas State Federal University, Brazil). The study, with a qualitative approach, had a semi-structured interview as a technique for collecting data that was transmitted in the light of the content analysis method. The data showed that the academic-pedagogical challenges include the lack of adequate resources and spaces for the interconnection of theory and practice with the dormant interest of students towards teaching training courses. However, the incentive and awareness attitudes made the difference in favor of the students' success, added to the strategies of the pedagogical practices seen as possibilities to overcome the challenges, as well as the work in partnership with the peers as well as the socialization of experiences, which was relevant in this context.